Efficacy of celiac plexus block in chronic pancreatitis in pediatric age group - Syam, Divya; Gajanthody, Suhitha; Kulkarni, Rammurthy; Ahmed, Ashraf (Indian Journal of Child Health, 2019)
Neurolysis of the celiac plexus has been found to be an effective way of palliating chronic pain due to non-pelvic intra-abdominal organ pathologies such as upper abdominal malignancies and chronic pancreatitis. We assessed the effectiveness of celiac plexus block (CPB) for pain due to chronic pancreatitis in pediatric age group. Eleven children between the age group of 3–10 years suffering from abdominal pain due to chronic pancreatitis underwent CPB through transaortic approach. Assessment of pain relief compared to pre-procedure status was done using Wong-Baker Faces Pain Rating Scale. Ten out of 11 children had symptomatic relief post-procedure and on 6 months follow-up. One child had relapse of pain after 3 months of CPB. We conclude that CPB is a promising solution for tackling intractable pain due to chronic pancreatitis in pediatric age group.